Dendrimer sebagai Sistem Penghantaran Obat Terapi Kanker Payudara - Azmi Aziz; Aulia Fikri Hidayat; Ratih Aryani (UNISBA Press, 2024)
Abstract. Breast cancer is one of the most common types of cancer in women and a leading cause of cancer-related deaths over the past two decades. Current breast cancer therapies using anticancer drugs face challenges such as non-specific toxicity, poor drug solubility, and low bioavailability. Dendrimers, as drug delivery systems, offer potential solutions to these issues. Dendrimers are branched polymers with controllable structures that allow for more effective and targeted drug delivery. This study aims to explore dendrimer synthesis, characterize dendrimers as potential breast cancer drug delivery systems, and evaluate their cytotoxicity against breast cancer cells. A systematic literature review of 11 journals revealed that dendrimers can be synthesized using the divergent method with base materials like NH₃ or ethylenediamine (EDA). Dendrimers are effective as drug delivery systems due to their spherical shape, size under 100 nm, loading efficiency of 61.8%, and low cytotoxicity in normal cells. However, they exhibit high cytotoxicity against cancer cells, with a cell viability of 27.1%. Abstrak. Kanker payudara adalah jenis kanker yang paling umum pada wanita dan merupakan penyebab utama kematian akibat kanker selama dua dekade terakhir. Terapi dengan obat antikanker menghadapi tantangan seperti toksisitas non-spesifik, kelarutan obat yang buruk, dan bioavailabilitas rendah. Dendrimer, sebagai sistem penghantaran obat, menawarkan solusi untuk mengatasi masalah ini. Dendrimer adalah polimer bercabang dengan struktur yang dapat dikendalikan, memungkinkan pengiriman obat yang lebih efektif dan spesifik. Penelitian ini bertujuan untuk mengkaji sintesis, karakteristik, dan sitotoksisitas dendrimer terhadap sel kanker payudara. Melalui tinjauan pustaka dari 11 jurnal, ditemukan bahwa dendrimer dapat disintesis menggunakan metode divergen dengan bahan dasar seperti NH₃ atau etilendiamin (EDA). Dendrimer efektif sebagai sistem penghantaran obat dengan karakteristik bulat berukuran kurang dari 100 nm, efisiensi pemuatan 61,8%, dan sitotoksisitas rendah pada sel normal, namun menunjukkan sitotoksisitas tinggi terhadap sel kanker dengan viabilitas sel 27,1%.